An Analysis of Idiomatic Expressions Found In The Story Entitled The Car by Andrew Rossiter: English - Wasti Jumetan; Rocky P. Sekoni; Oce A. Langkameng; Yanrini Martha Anabokay (Universitas Persatuan Guru 1945 NTT, 2026)
This study are to identify the types of idiomatic expressions and to analyze their meanings found in the short story The Car. This research used a descriptive qualitative method because the data were analyzed in the form of words, phrases, and sentences rather than numbers. The findings showed that there were 25 idiomatic expressions found in the story. They consisted of 11 pure idioms, 8 semi idioms, and 6 literal idioms. Pure idioms became the most dominant type because many expressions in the story had figurative meanings that could not be understood literally. Expressions such as “goes like a dream,” “well up,” and “write-off” reflected emotional situations and strengthened the dramatic atmosphere of the story. Meanwhile, semi idioms and literal idioms helped make the conversations sound more natural and realistic.